Investigating the role of drama in two enabling courses in Australia. Issue 1 (1st August 2019) - Carter, Carol; Sallis, Richard
This article discusses the use of drama as a method for teaching and learning using two case studies from different geographical locations and teaching contexts in Australia. The first, from the University of Newcastle, is in the field of enabling education that supports students to gain the knowledge and skills required to continue their journey to a higher education degree. The other, from an existing university pre-service teaching programme at the University of Melbourne, supports students to gain the knowledge and skills required to enter the teaching profession in an Australian context. Both case studies, which are also part of a broader, ongoing research project, examine the role drama can play in the creation of supportive dialogical spaces for learning in higher education contexts, where the students come from a diverse range of socio-cultural backgrounds. The qualitative research is framed by practitioner research, pedagogical methodology and ethnodrama. Dramatized dialogue is used to share our findings. To date, our research has revealed that drama education techniques and activities, and the use of ethnodrama, can both enhance student participation and engagement, and contribute to successfully achieving the aims and objectives of the respective programmes.